Administracja samorządowa i rządowa (nowy model administracji państwowej?) - Rabska, Teresa (Wydział Prawa i Administracji UAM, 1991)
The conception of local self-government contained in the law of March 8, 1990, refers to the tradition of Polish self-government and yet meets the requirements provided for in the European Local Government Charter. The .atbove makes it possible, on the one hand, to return to the institutions previously known to the Polish law, and, on the other, to compare them with their European counterparts. The re-instatement of self-government has brought back to light the issue of duality of public administration and its division into government and selfgovernment administration. In view of the principle in force in the former political regime namely the principle of „unity of government on the level of a locality, the solution to the problem of duality is far from easy". New legislation creates grounds for a new, structurally diversified model of state administration. At the Województwo level (the highest unit of local organization), there operates a nominated official, Wojewoda, the organ of government administration, whereas at a local level — in gmina — the ,,basic form of organization of public activity" is local self-government. The duality of administration manifests itself in many legislative acts. The most important of them are: the Act on Local Self-Government and the Act on Government Administration; mention should also be made about the Act on division of tasks and powers between various organs representing basically different types of administration, etc. Some issues posed by the model require further amendments. Problems of particular gravity arise in connection with the question of regions as subsidiary units of basic administrative division of the country, created to further the tasks of government administration at a local level, the absence of deep structural reforms at a central government level, the absence of a clear determination of position of government administration vis-a vis self-government, disputable budgetary and financial solutions, etc. All this leads to the conclusion that the legislative conception of duality of state administration is not sufficiently clear. Neverheless, it is beyond doubt that the new structure of administration is presently in its formative period.
Self-government and government administration (A new model of state administration?)